Processing Capabilities Of Micro Ultrasonic Machining For Hard And Brittle Materials: SPH Analysis And Experimental Verification - Jingsi, Wang; Liew, Pay Jun; Jinlong, Wang; Fengming, Du; Keita, Shimada (Elsevier Inc., 2020)
Micro ultrasonic machining (micro-USM) is an unconventional micromachining technology that has capability to fabricate high aspect ratio micro-holes, intricate shapes and features on various hard and brittle materials. The material removal in USM is based on brittle fracture of work materials. The mechanical properties and fracture behaviour are different for varied hard and brittle materials, which would make a big difference in the processing capability of micro-USM. To study the processing capability of USM and exploit its potential, the material removal of work materials, wear of abrasive particles and wear of machining tools in USM of three typical hard and brittle materials including float glass, alumina, and silicon carbide were investigated in this work. Both smoothed particle hydrodynamics (SPH) simulations and verification experiments were conducted. The material removal rate is found to decrease in the order of glass, alumina, and silicon carbide, which can be well explained by the simulation results that cracking of glass is faster and larger compared to the other materials. Correspondingly, the tool wear rate also dropped significantly thanks to the faster material removal, and a formation of concavity on the tool tip center due to intensive wear was prevented. The SPH model is proved useful for studying USM of different hard and brittle materials, and capable of predicting the machining performance